EXPLORING THE PORTRAYAL OF ISLAMIC ETHICAL VALUES IN SENIOR HIGH SCHOOL EFL TEXTBOOKS: A CRITICAL DISCOURSE ANALYSIS - Afandi, Ahmad Fauzi; Basya, Dihliza; Fauzi, Fatih Al (Denpasar Institute, 2025)
In global contemporary education, where character development and ethical growth are acknowledged as integral components, the incorporation of moral and ethical values in textbooks assumes paramount significance. However, in the context of Indonesian schools, especially Islamic institutions, government-endorsed English as a Foreign Language (EFL) textbooks often lack alignment with religious values, particularly Islamic ethics. This critical discourse analysis study aims to investigate the representation of Islamic ethics values in the EFL textbooks sanctioned by the Indonesian Ministry of Education and Culture for Islamic Senior High Schools. Employing language appraisal theory and visual grammar theory, the research evaluates the extent to which the content aligns with Islamic ethics values within the framework of Indonesian religious norms. This study highlights the need for further research on Islamic ethics values within Indonesian English Language Teaching (ELT) textbooks, a step toward fostering a deeper understanding of Islamic principles in ELT contexts. The findings of this study demonstrate that the EFL textbook effectively incorporates Islamic ethic values, including kindness, being friendly and polite, and respecting boundaries, consistently throughout the text. Both visual and verbal texts illustrate how these values are integrated into current topics to nurture moral development among students. In addition, the inclusivity of these textbooks exceeds expectations, as they are designed for all senior high schools without targeting any specific group. Nevertheless, it successfully instils Islamic ethical values, emphasizing their significance in shaping students' moral awareness and behaviour in diverse social interactions. The implication of this study is a deeper understanding of the current state of EFL textbooks in relation to Islamic ethical values, adding to the empirical knowledge base in the field of education.